Influence of the Scrap Tyre Processing Techniques on the Physical Properties of the Crumb Rubber - Naeem Aziz Memon; Kamran Ansari; Zaheer Ahmed Almani (Mehran University Research Journal of Engineering and Technology, 2012)
The processing mechanism of scrap tyres to produce CR (Crumb Rubber) has a great influence on the properties of the CRMB (Crumb Rubber Modified Bitumen). A fair amount of research was observed in the literature on the bitumen modified by CR processed cryogenically and ambiently. However, little or no work has been done on the CR processed by the other methods such as the Aquablast processing technique, which is a relatively a new waste tyre rubber processing technique within the CR industry. In this study, CR obtained from the two sources; ambient and Aquablast grinding techniques were primarily assessed with a helium pycnometer and SEM (Scanning Electron Microscopy) for their physical properties and appearance respectively. Observations from this laboratory study indicated: (1) the density of the ambient CR was slightly higher than the CR obtained from Aquablast technique; (2) difference in physical appearance was found insignificant.